2022
DOI: 10.1371/journal.pone.0276342
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional fractal dimension and lacunarity features may noninvasively predict TERT promoter mutation status in grade 2 meningiomas

Abstract: Purpose The 2021 World Health Organization classification includes telomerase reverse transcriptase promoter (TERTp) mutation status as a factor for differentiating meningioma grades. Therefore, preoperative prediction of TERTp mutation may assist in clinical decision making. However, no previous study has applied fractal analysis for TERTp mutation status prediction in meningiomas. The purpose of this study was to assess the utility of three-dimensional (3D) fractal analysis for predicting the TERTp mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…In our own series, we further demonstrated a para-sagittal tumor location as a strong predictor for TERT promotor mutations in high-grade meningiomas [19]. Similarly, three-dimensional fractal dimension and lacunarity features were previously shown to strongly correlate with TERT promotor mutation status [29], further underlining the immense potential of imaging characteristics to predict molecular alterations in general, and especially of TERT, in meningiomas. However, investigator-based imaging analyses typically suffer from subjectivity and subsequent inter-observer variability and are mostly restricted to small patient cohorts.…”
Section: Discussionsupporting
confidence: 65%
“…In our own series, we further demonstrated a para-sagittal tumor location as a strong predictor for TERT promotor mutations in high-grade meningiomas [19]. Similarly, three-dimensional fractal dimension and lacunarity features were previously shown to strongly correlate with TERT promotor mutation status [29], further underlining the immense potential of imaging characteristics to predict molecular alterations in general, and especially of TERT, in meningiomas. However, investigator-based imaging analyses typically suffer from subjectivity and subsequent inter-observer variability and are mostly restricted to small patient cohorts.…”
Section: Discussionsupporting
confidence: 65%
“…We hypothesize that FD can provide valuable information that correlates with the genotype and phenotype of a tumor. Existing studies on fractal analysis have shown promising results, including predicting TERTp mutation status in meningiomas [1], prediction of prostate cancer grade [2], etc. To our knowledge, there has been no study applying fractal analysis to IDH mutation status prediction, although there was a recent study using radiomics to predict IDH mutation with MGMG promoter methylation subtype [3].…”
Section: Introductionmentioning
confidence: 99%